Septal Bulge and Risk of Paravalvular Leak After Transcatheter Aortic Valve Replacement. Issue 4 (4th July 2019) - Sanchis, Laura; Nijenhuis, Vincent J.; Post, Marco C.; Van Der Heijden, Jan As; Rensing, Benno J.; Ten Berg, Jürien M.; De Kroon, Thom L.; Brouwer, Jorn; Heijmen, Robin H.; Swaans, Martin J.
ABSTRACT: Background: Proximal septal bulge (SB) is a subaortic protuberance of the interventricular septum into the left ventricular outflow tract (LVOT) without extension to the middle and distal septum. Our aim was to evaluate the impact of SB presence on the incidence of paravalvular leak (PVL) after transcatheter aortic valve replacement (TAVR) in a hypothesis-generating study. Methods: Patients who underwent TAVR in a single center were screened. Those patients with non self-expanding devices with annular leaflet position (Edward Sapien, Lotus) or self-expanding prosthesis and supra-annular leaflet design (Evolut, CoreValve) were included; devices in the early learning curve were excluded. Transesophageal echocardiography (TOE) images performed during TAVR were reviewed and SB nonstandard measurements were obtained from LVOT view. The presence of PVL was evaluated in the TOE immediately after TAVR. ANOVA and Bonferroni statistical tests were used to compare quantitative variables among groups. Results: We included 147 patients (mean age 78 ± 12 years, 59% females). The implanted devices were: 33 Evolut R, 56 CoreValve, 41 Lotus Valve and 17 Edwards Sapien. There were no significant differences between SB parameters among the different devices. Maximal SB thickness in the LVOT was related to PVL grade in the self-expanding valves. Moderate-severe PVL was less frequently observed in the non self-expanding devices group (2.4%), the differences among this group were not significant. Conclusions: The presence of a prominent SB in the LVOT could be related to a higher risk of PVL, likely in self-expandable devices with supra-annular leaflet position.